Differences in the impact of R&D intensity and R&D internationalization on firm performance – Mediating role of innovation performance - Leung, Tak Yan; Sharma, Piyush (Elsevier, 2021)
This paper investigates the mediating role of innovation performance in the effects of R&D intensity and R&D internationalization on firm performance, using 1540 firm-year observations from a balanced panel of 385 privately-owned firms listed on the Shanghai and Shenzhen stock exchanges. Results show a negative effect of R&D intensity on short-term (profitability) and positive effect on long-term (firm value) financial performance but no significant effect on export (sales) performance. In contrast, R&D internationalization has a positive effect on export performance but no significant effect on short- or long-term financial performance. Moreover, innovation performance (number of patents) partially mediates the impact of R&D intensity and R&D internationalization on firm performance and these effects vary based on firm age and size. Besides extending current literature on R&D investments, these results have useful implications for firms especially those from emerging markets with international R&D operations or those aiming to internationalize their R&D activities.